Lateralized auditory cortical alpha band activity and interregional connectivity pattern reflect anticipation of target sounds - Müller, Nadia; Weisz, Nathan (Cerebral Cortex, 2012)
The anticipation of stimuli facilitates the top-down preparation of neuronal tissue involved in the processing of forthcoming targets. Increasing evidence in the visual modality emphasizes the anticipatory adjustment of visual cortex excitability through modulations of oscillatory alpha power. In the auditory system, however, this relationship has not yet been established. Furthermore, the association between anticipatory modulations of auditory alpha power and a potential top-down network within these anticipatory preparation processes remains unexplained. To disclose these processes, we recorded magnetoencephalography while visually cuing participants to attend to either ear and to anticipate forthcoming auditory stimuli. For the cue-stimulus phase, we expected an asymmetric modulation of auditory alpha power when attending to the left or right ear, assuming that frontoparietal regions would phase synchronize with the auditory cortex in an asymmetric pattern. Beamformer source solutions demonstrate an asymmetric modulation of auditory alpha power following visual cues expressed in a strong right auditory alpha power increase when attending to the right ear. Furthermore, the right auditory cortex is functionally connected to the frontal eye fields during the ipsilateral alpha increase. Altogether, these results contribute significantly to the understanding of how auditory anticipation acts on a local as well as on a network level. © 2011 The Author.
Created from Fastlane, Scopus look-up
Keywords: frontal eye field; MEG; phase coupling; spatial attention; synchronization